2019
DOI: 10.3390/antiox8110548
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Increases Endogenous Complement-Dependent Inflammatory and Angiogenic Responses in Retinal Pigment Epithelial Cells Independently of Exogenous Complement Sources

Abstract: Oxidative stress-induced damage of the retinal pigment epithelium (RPE) and chronic inflammation have been suggested as major contributors to a range of retinal diseases. Here, we examined the effects of oxidative stress on endogenous complement components and proinflammatory and angiogenic responses in RPE cells. ARPE-19 cells exposed for 1–48 h to H2O2 had reduced cell–cell contact and increased markers for epithelial–mesenchymal transition but showed insignificant cell death. Stressed ARPE-19 cells increase… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
57
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(70 citation statements)
references
References 65 publications
8
57
0
Order By: Relevance
“…FH downregulation leads to an increase in C3 mRNA levels, followed by accumulation of C3 in the extracellular compartment. In parallel, we detected a slight reduction of secreted FH after H 2 O 2 pre-treatment, a phenomenon previously observed in H 2 O 2 -treated ARPE19 cells 53 . In the afore mentioned study, in which RPE cells were treated with 500 µM H 2 O 2 , FH accumulates intracellularly, while in a different study, exposure to a mild and short oxidative insult (150 µM for 90 minutes) does not result in intracellular accumulation 54 .…”
Section: Discussionsupporting
confidence: 85%
“…FH downregulation leads to an increase in C3 mRNA levels, followed by accumulation of C3 in the extracellular compartment. In parallel, we detected a slight reduction of secreted FH after H 2 O 2 pre-treatment, a phenomenon previously observed in H 2 O 2 -treated ARPE19 cells 53 . In the afore mentioned study, in which RPE cells were treated with 500 µM H 2 O 2 , FH accumulates intracellularly, while in a different study, exposure to a mild and short oxidative insult (150 µM for 90 minutes) does not result in intracellular accumulation 54 .…”
Section: Discussionsupporting
confidence: 85%
“…Immunostaining was performed as described previously [ 22 ]. PBS-washed, paraformaldehyde-fixated (4%, 20 min; Merck, # 100496) hpRPE cells were blocked 3% BSA (Carl Roth, Karlsruhe, Germany, #8076/ PBS-T, 1 h).…”
Section: Methodsmentioning
confidence: 99%
“…The RPE acts as a regulatory, secretory epithelium supporting the retina. It locally secretes complement components as C1q, complement factor B (CFB), complement component 4 (C4), CFI, and CFH [ 20 , 21 , 22 , 23 ]. We and others showed that complement secretion is modified by external stress [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress and chronic inflammation are also responsible for the damage to retinal pigment epithelium (RPE) that contribute to several retinal degenerative diseases, such as age-related macular degeneration or Stargardt disease. Trakkides et al [5], for the first time, reported that oxidative stress induced an increased expression of the complement regulators (CFH) and properdin and the central complement protein C3 in RPE cells independent of an external complement source. These increases are, on the other hand, associated with inflammasome activation that, subsequently, enhanced secretion of proinflammatory and proangiogenic factors.…”
mentioning
confidence: 99%